Age at Menopause, Reproductive Life Span, and Type 2 Diabetes Risk - Brand, Judith S.; van der Schouw, Yvonne T.; Onland-Moret, N. Charlotte; Sharp, Stephen J.; Ong, Ken K.; Khaw, Kay-Tee; Ardanaz, Eva; Amiano, Pilar; Boeing, Heiner; Chirlaque, Maria-Dolores; Clavel-Chapelon, Françoise; Crowe, Francesca L.; et al. (Diabetes care, 2013)
OBJECTIVE-Age at menopause is an important determinant of future health outcomes, but little is known about its relationship with type 2 diabetes. We examined the associations of menopausal age and reproductive life span (menopausal age minus menarcheal age) with diabetes risk. RESEARCH DESIGN AND METHODS-Data were obtained from the InterAct study, a prospective case-cohort study nested within the European Prospective Investigation into Cancer and Nutrition. A total of 3,691 postmenopausal type 2 diabetic case subjects and 4,408 subcohort members were included in the analysis, with a median follow-up of 11 years. Prentice weighted Cox proportional hazards models were adjusted for age, known risk factors for diabetes, and reproductive factors, and effect modification by BMI, waist circumference, and smoking was studied. RESULTS-Mean (SD) age of the subcohort was 59.2 (5.8) years. After multivariable adjustment, hazard ratios (HRs) of type 2 diabetes were 1.32 (95% CI 1.04-1.69), 1.09 (0.90-1.31), 0.97 (0.86-1.10), and 0.85 (0.70-1.03) for women with menopause at ages <40, 40-44, 45-49, and >= 55 years, respectively, relative to those with menopause at age 50-54 years. The HR per SD younger age at menopause was 1.08 (1.02-1.14). Similarly, a shorter reproductive life span was associated with a higher diabetes risk (HR per SD lower reproductive life span 1.06 [ 1.01-1.12]). No effect modification by BMI, waist circumference, or smoking was observed (P interaction all > 0.05). CONCLUSIONS-Early menopause is associated with a greater risk of type 2 diabetes. Diabetes Care 36:1012-1019, 2013